“IN LITERATURE, HE IS AN EXTRAORDINARY ARTIST”: THE INTERMEDIAL EMPHASES OF LITERARY RECEPTIONS OF VASYL STEFANYK’S - Mocherniuk, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The paper provides an overview of literary studies focusing on the work of Vasyl Stefanyk, in which the reception of short stories draws on vocabulary from different visual arts. In their efforts to unravel the secrets of the writer’s style, scholars often consciously or intuitively compare his artistic style to other arts, using their toolkit. Stepan Smal-Stotsky, Olha Kobylianska, Lesia Ukrainka, Ivan Franko, Bohdan Lepky, Antin Krushelnytskyi, Serhii Yefremov, Ivan Trush, Alexandra Chernenko, Yulian Vassyian, Mykhailyna Kotsyibynsky as well as many current scholars resort to comparisons with graphics, painting, photography and architecture. The focus is on this distinctive perception of the writer’s poetics in connection with attempts to explain his aesthetic and artistic strands. The importance of J. Vassian’s conclusion, whісh considers the artistic world of the writer in comparison with Wagner’s Gesamtkunstwerk, a synthetic and comprehensive work of art, is emphasized. Such a literary vision has a significant interpretive potential in the intermedia aspect and requires further scientific development. It is proved that Stefanyk's artistic word gives impulses to other arts. The latest evidence of this already applies to the art of cinema. Stefanyk is potentially extremely cinematic, as evidenced by modern researchers in their publications. Vasyl Stefanyk’s short stories are thus endowed with a great power of influence on other types of art, which should be traced in the following studies.